Catalogue of Turkish Manuscripts in the Library of Leiden University and Other Collections in the Netherlands Minor Collections - Schmidt, Jan (c6adfee8-e883-410f-bb4a-d85d86dcf688, 2012)
The present catalogue is the fourth and final volume in a series that covers the Turkish manuscripts preserved in public libraries and museums in the Netherlands. This volume gives detailed descriptions of Turkish manuscripts in minor Dutch collections, found in libraries and museums in Leiden, Utrecht, Groningen and other towns. Readership: All those interested in (oriental) manuscripts and the history and culture of the Turks and the Ottoman Empire, but in particular scholars using Turkish manuscripts as sources for their research.